The Rapid and Reliable Method to Assess the Blackgram (Vigna mungo (l.) Hepper) Genotypes for Thermotolerance - Partheeban, C.; Vijayaraghavan, H.; Boominathan, P. (International Journal of Bio-resource and Stress Management, 2023)
High temperature stress in plants reduces crop yield because it negatively affects several plant physiological processes, including photosynthesis, respiration, growth, development and partitioning. Pulses are more sensitive to high temperature stress at reproductive stage. Blackgram is an important source of protein and widely used in daily diet. In this study, lethal temperature and induction temperature was standardized for blackgram genotypes by using Temperature Induction Response (TIR) technique. The standardization of induction temperature and lethal temperature is based on per cent growth reduction and survival percentage at the end of recovery period. The induction temperature was standardized as 36 to 46 °C for 3 h and the lethal temperature as 52 °C for 3 h. A total of nineteen blackgram genotypes were screened and evaluated for thermo tolerance. By using standardized optimum induction and challenging temperature, cellular level tolerance was assessed in all the blackgram genotypes. Based on root length and shoot length of induced seedlings over control seedlings, the cellular level tolerance in terms of least reduction in growth and highest survival percentage was calculated. Also, the physiological basis of thermo tolerance was assessed by measuring the proline content and antioxidant enzyme activities. Thermotolerant genotypes show higher survival percentage and lower growth reduction. Further the tolerant genotypes identified based on TIR also showed higher antioxidant enzymes activity implying the critical role of antioxidant in cellular thermotolerance. The genotypes VBG-07-001, VBG-06-010 has shown intrinsic heat tolerance and therefore they can be explored as donor source in breeding programme aimed for global warming.